Pengaruh Model Kooperatif Tipe Student Teams Achievement Division (STAD) Terhadap Motivasi Belajar Siswa pada Pembelajaran Sejarah di Kelas XI IPS SMAN 1bangun Purba, Rokan Hulu - Ramadani, Putri; Isjoni, Isjoni; Asril, Asril (CV. Rayyan Dwi Bharata, 2025)
The background of this research is that there is a problem faced by students when studying history subjects in class XI IPS, Some students feel less motivated when studying history, then when the learning process takes place, students experience boredom and the learning model used has often been used, so it does not support students' activity during the learning process, learning is still lacking, so it does not support students' activity during the learning process. The problems studied in this research are: (1) How is the application of the Cooperative Model of the Student Teams Achievement Division (STAD)Type in History Learning in Class XI IPS SMAN 1 Bangun Purba, Rokan Hulu? (2) Is there an influence of the Cooperative Model of Student Teams Achievement Division (STAD) Type on History Learning in Class XI IPS SMAN 1 Bangun Purba, Rokan Hulu? (3) How Much Influence Does The Cooperative Model Of Student Teams Achievement Division (STAD) Type On Student Learning Motivation In History Learning In Class XI IPS SMAN 1 Bangun Purba, Rokan Hulu?. The method used in this research is the distribution of questionnaires to respondents of class XI IPS SMAN Bangun Purbawhich totals 46 students as well as questionnaire/questionnaire data collection techniques and documentation. The data analysis techniques used are Normality Test, Homogeneity and Test t using Team Quiz Variable (X) and Learning Interest Variable (Y). Based on the results of statistical analysis of Normality, Homogeneity and t Test, it was concluded that there is an influence of the Student Teams Achievement Division model on student learning motivation in learning history in class XI IPS SMAN 1 Bangun Purba.Judging from the average, the experimental class is higher than the control class. In the experimental class using the Student Teams Achievement Division model, the student learning motivation had an average of 81.1. The control class has an average student learning motivation score of 78.8.